KAJIAN PENERIMAAN SISTEM INFORMASI KEPESERTAAN DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL STUDI KASUS PADA DANA PENSIUN PLN - Apriyanto, Apriyanto (LPPM Universitas Nusa Mandiri, 2015)
Participant Information Systems of Pension Fund (SISKEP) is a subsystem information system of pension funds are built to answer the needs of data and information quickly and accurately in a Pension Fund industry in specially for data processing participant data in a pension fund. The most important for the implementation of an information system its is if the system can be a success and accepted by users. One indicator of the acceptance or no a system is to look at the benefits and ease in operating a system. Therefore, it is necessary to study how far the user's acceptance of a system in the implementation its. The research was conducted by using the approach of the Technology Acceptance Model (TAM). Sampling using a questionnaire completed by 60 respondents. Research purposes to determine the extent to which the level of user acceptance of the implementation participant Information Systems of Pension Fund of PLN in Jakarta with analyzing the influence perceived ease of use and perceived usefulness of the participant's acceptance of information systems. Data processing method using the Statistical Product and Service Solutions (SPSS). Research suggests shows that the ease and benefits factors in the Participants Information Systems of Pension Fund PLN significantly positive effect on user acceptance, so that when the level of perceived ease of use and perceived usefulness high, it will affect the level of user acceptance towards the implementation of the participant Information Systems.